2020
DOI: 10.1111/dom.14257
|View full text |Cite
|
Sign up to set email alerts
|

The majority of people with type 1 diabetes and multiple daily insulin injections benefit from using continuous glucose monitoring: An analysis based on the GOLD randomized trial (GOLD‐5)

Abstract: Aim To identify responders to continuous glucose monitoring (CGM) in relation to reductions in HbA1c and percentage of time spent in hypoglycaemia after initiation of CGM for individuals with type 1 diabetes treated with multiple daily insulin injections. Materials and Methods We analysed data from 142 participants in the GOLD randomized clinical trial. We evaluated how many lowered their HbA1c by more than 0.4% (>4.7 mmol/mol) or decreased the time spent in hypoglycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…baseline HbA1c >86 mmol/mol [>10%]). This agrees with DIAMOND 26 and GOLD 27 studies. Surprisingly, the rates of moderate and severe hypoglycaemia observed during the COACH study were lower than anticipated and far less than previously reported by studies such as the T1D Exchange Clinic Registry 6 or DIALOG.…”
Section: Discussionsupporting
confidence: 92%
“…baseline HbA1c >86 mmol/mol [>10%]). This agrees with DIAMOND 26 and GOLD 27 studies. Surprisingly, the rates of moderate and severe hypoglycaemia observed during the COACH study were lower than anticipated and far less than previously reported by studies such as the T1D Exchange Clinic Registry 6 or DIALOG.…”
Section: Discussionsupporting
confidence: 92%
“…Automated insulin delivery systems can offer CGM users additional support, including algorithm-based calculations of predicted future glucose values and automatically adjusted insulin doses to reduce hypoglycemia 3. However, clinically significant hypoglycemia, such as level 2 hypoglycemia (ie, blood glucose levels <54 mg/dL or <3 mmol/L) or severe hypoglycemia (where cognitive or physical dysfunctions develop and assistance for administering treatment is required4), continues to affect about 15%–35% of people with type 1 diabetes (T1D) despite use of these advanced technologies 5–10…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiology/complications required 4 ), continues to affect about 15%-35% of people with type 1 diabetes (T1D) despite use of these advanced technologies. [5][6][7][8][9][10] Qualitative studies have expanded knowledge of patients' perspectives on using CGMs, [11][12][13] outlined barriers to hypoglycemia self-management in non-CGM users, 14 15 and improved understanding of the roles of complex cognitive-behavioral 16 17 and psychosocial 18 factors in hypoglycemia management. However, limited research has described the hypoglycemia selfmanagement process among advanced diabetes technology users.…”
mentioning
confidence: 99%